Optimization of Ct-Spn Anatomical Image of Coronal Section With Slice Thickness Reconstruction Variations and Increment Reconstruction in Rhinosinusitis Cases Chronic at Rs Balimed - Ririn Eri Kastiwi (International Journal Labs, 2022)
Background: One of the modalities used to diagnose rhinosinusitis is CT Scan. In CT Scan, there are several parameters, namely slice thickness and reconstruction increment. Objective: aims to determine the optimization of the CT-SPN anatomical image produced with variations in slice thickness and reconstruction Methods: This type of research is a quantitative study with an experimental approach conducted at Balimed Hospital from July to August 2022. Results: Friedman test results for the whole anatomy showed a significance p of 0.0001 (p value <0.05) which means Ho is rejected and Ha is accepted which means that there is a significant difference in the anatomical image information of CT Scan of the paranasal sinuses in coronal sections with variations in slice thickness reconstruction and incremental reconstruction in chronic rhinosinusitis. And based on the Wilcoxon test, it also showed that each variation had a p value <0.05, which means that there are differences in anatomical image information for each variation. Conslusion: The conclusion of this study, based on this study, shows that there are differences in information on the coronal CT-SPN anatomical image with variations in slice thickness and increment reconstruction in cases of chronic rhinosinusitis and variation 2 has the most optimal anatomical image information. Based on the Wilcoxon test, it also shows that each variation has different anatomical image information.